2010
DOI: 10.1007/s13157-010-0043-9
|View full text |Cite
|
Sign up to set email alerts
|

Wetland-Groundwater Interactions in Subtropical Depressional Wetlands

Abstract: Restoration of ditched and drained wetlands in the Lake Okeechobee basin, Florida, USA is currently under study for possible amelioration of anthropogenic phosphorus enrichment of the lake. Here we focus on the dynamic hydrology of these systems, with emphasis on understanding the interaction between wetland surface water and adjacent upland groundwater. Based on natural drawdown events observed over 2 years at four depressional wetlands, hydraulic conductivities (K) of the soils surrounding the wetlands were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 23 publications
(23 reference statements)
1
29
0
Order By: Relevance
“…Results of this study reinforce the findings (e.g., Dunne et al 2006;Cohen et al 2007;Dunne et al 2010;Bhadha and Jawitz 2010;Min et al 2010) that GIWs of the Florida peninsula have a high potential to retain P, but with the retention comes the possibility that the P sink may become a P source when runoff enters the GIW with values\EPC 0 . For instance, Yu et al (2006) reported P in runoff over 44 rain events across five Florida citrus grove sites to range from 0.51 to 2.64 mg P L -1 , sufficiently below our measured EPC 0 value to suggest that each event would cause a release of P to the water column, further increasing the P concentration.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Results of this study reinforce the findings (e.g., Dunne et al 2006;Cohen et al 2007;Dunne et al 2010;Bhadha and Jawitz 2010;Min et al 2010) that GIWs of the Florida peninsula have a high potential to retain P, but with the retention comes the possibility that the P sink may become a P source when runoff enters the GIW with values\EPC 0 . For instance, Yu et al (2006) reported P in runoff over 44 rain events across five Florida citrus grove sites to range from 0.51 to 2.64 mg P L -1 , sufficiently below our measured EPC 0 value to suggest that each event would cause a release of P to the water column, further increasing the P concentration.…”
Section: Resultssupporting
confidence: 84%
“…Thus, it is the hydrologic dis-connectivity of the GIWs which provides a service to downstream waters by retaining P. Maintaining an adequate hydroperiod in GIWs would support the development of OM in these wetland systems, which would likely increase the P storage capacity, or at the very least, decrease the mineralization rates for OM, keeping P in OM complexes. OM accretion, though low in depressional wetlands when compared with systems adjacent to flowing water systems (Craft and Casey 2000), would provide for long-term burial of P, further supporting the maintenance of hydrology in these wetland systems, which in some cases (e.g., in Florida) have been noted to stay inundated for 64-86 % of a two to three-year study period (Min et al 2010). Forested wetlands had higher organic content than emergent marsh systems, which was also correlated with higher P sorption in PFOs.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…It occurs via unidirectional, episodic, and transient surface connections when depression storage is seasonally filled (e.g., vernal pools) (42,65), or via slower moving subsurface flow paths (58,66,67). Despite uncertainty in quantifying timescales of hydrologic connectivity, GIWs have recently been shown to regulate (68,69) and stabilize (70) potentiometric gradients that generate base flow in streams. These subsurface flow paths may be hard to see (71), but they are not speculative or insubstantial connections.…”
Section: Landscape Connectivitymentioning
confidence: 99%
“…Depressional wetlands in the LOB are seasonally inundated and may experience multiple wetting/drying cycles as the regional water table rises/ falls. In a 2-year study of four isolated wetlands in the LOB, Min et al (2010) found mean annual hydroperiods of 71±10% with groundwater inflow occurring 15% of the time the wetlands were inundated. The inflowing shallow groundwater (pore water) may act as a potential internal advective source of P.…”
Section: Background and Motivationmentioning
confidence: 99%